1993
DOI: 10.2134/jpa1993.0207
|View full text |Cite
|
Sign up to set email alerts
|

Tillage and Crop Rotation Affect Corn, Soybean,and Winter Wheat Yields

Abstract: There is little research in northern regions on tillage systems in corn (Zea mays L.), soybean [Glycine max(L.) Merr], and wheat (Triticum aestivum L.) rotations. The objectives of this study were to (i) evaluate the influence of tillage on performance of corn, soybean, and winter wheat in rotations with each other, and (ii) determine whether corn or soybean yields could be increased in 3‐yr rotations with wheat compared with an annual rotation with each other. Field studies were conducted near Arlington, WI, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 22 publications
7
68
1
Order By: Relevance
“…practices (Griffith et al, 1988;Lund et al, 1993;AdvientoBorbe et al, 2007). Most previous studies on rotation effect were conducted on research stations or on-farm field trials conducted for a limited number of site-years, where crops were managed following "recommended" or "best" farm management practices.…”
Section: Core Ideasmentioning
confidence: 99%
See 1 more Smart Citation
“…practices (Griffith et al, 1988;Lund et al, 1993;AdvientoBorbe et al, 2007). Most previous studies on rotation effect were conducted on research stations or on-farm field trials conducted for a limited number of site-years, where crops were managed following "recommended" or "best" farm management practices.…”
Section: Core Ideasmentioning
confidence: 99%
“…The SPC1 and SPC2 are biophysical indicators of field-to-field variability and WPC1 and WPC2 are indicators of years' weather variability; hence, we decided to use these factors in the model instead of field and year as individual factors and, similarly, their interactions with crop sequence were included. For example, rotation effect on yield can be amplified in no-tilled maize fields, with heavy residue from prior high-yield maize crop, due to sowing and emergence delays, especially in years with earlyseason low temperature and high precipitation (Lund et al, 1993). Likewise, applied N fertilizer was also included in the model because maize grown in rotation with soybean typically receives less amount of N fertilizer compared with applied N fertilizer to maize grown after maize (Gentry et al, 2001).…”
Section: Identification Of Sources Of Variation For Rotation Effectmentioning
confidence: 99%
“…While the positive impacts of NT for environmental health through C sequestration, improving soil biological activity, soil structure, and soil water conservation were frequently reported (Hobbs et al, 2008;Six et al, 2002, FAO, 2011, Busari et al, 2015, the short-and long-term yield benefi ts from NT and CT have been mixed, that is, both, better yield from NT compared with CT (Endale et al, 2008;Toliver et al, 2012;Farooq et al, 2011) and better yield from CT compared with NT were reported (Davidson and Santelmann, 1973;Lund, 1993;MacHado et al, 2007). Perhaps that has contributed to slower adoption of NT technologies.…”
mentioning
confidence: 99%
“…Previous studies have shown that, for various reasons, continuous soybean cultivation involves significant yield decrease in the long-term (Crookston et al, 1991;Kelley et al, 2003;Meese et al, 1991), has negative effects on soil water balance (SaladoNavarro and Sinclair, 2009), influences soil chemical properties, and increases disease pathogens. However, the benefits of crop rotation depend on which crops are included in the rotation, and in which sequence (Lund et al, 1993). Unfortunately, it has been impossible to obtain detailed information about the precise number of rotation sequences and schemes which have been used over years.…”
Section: Sample Characteristicmentioning
confidence: 99%